2018
DOI: 10.1007/s00122-018-3126-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural chromosome rearrangements and polymorphisms identified in Chinese wheat cultivars by high-resolution multiplex oligonucleotide FISH

Abstract: High-resolution multiplex oligonucleotide FISH revealed the frequent occurrence of structural chromosomal rearrangements and polymorphisms in widely grown wheat cultivars and their founders. Over 2000 wheat cultivars including 19 founders were released and grown in China from 1949 to 2000. To understand the impact of breeding selection on chromosome structural variations, high-resolution karyotypes of Chinese Spring (CS) and 373 Chinese cultivars were developed and compared by FISH (fluorescence in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 33 publications
2
73
0
Order By: Relevance
“…After GISH, the hybridization signals were washed off with PBS (phosphate-buffered saline). Eight single-strand oligonucleotides were then used as probes for dual-color ND-FISH [36,39]. The eight oligonucleotides includes Oligo-pAs1-1, Oligo-pAs1-3, Oligo-pAs1-4, Oligo-pAs1-6, Oligo-AFA-3, Oligo-AFA-4, Oligo-pSc119.2-1 and Oligo-(GAA) 10.…”
Section: Methodsmentioning
confidence: 99%
“…After GISH, the hybridization signals were washed off with PBS (phosphate-buffered saline). Eight single-strand oligonucleotides were then used as probes for dual-color ND-FISH [36,39]. The eight oligonucleotides includes Oligo-pAs1-1, Oligo-pAs1-3, Oligo-pAs1-4, Oligo-pAs1-6, Oligo-AFA-3, Oligo-AFA-4, Oligo-pSc119.2-1 and Oligo-(GAA) 10.…”
Section: Methodsmentioning
confidence: 99%
“…Allopolyploid genome plasticity, together with heterosis, may play an important role in the success of some allopolyploid lineages, relative to their diploid progenitors (Feldman and Levy 2012;Van de Peer et al 2017). Large-scale genomic rearrangements between wheat allopolyploids (Devos et al 1995;Badaeva et al 2007;Jorgensen et al 2017;Huang et al 2018;Thind et al 2018) and between wheat allopolyploids and their progenitor species Huo et al 2018) were previously identified. However, the mechanisms involved in such rearrangements remain largely unknown.…”
Section: The Dynamic Nature Of the Wheat Genomementioning
confidence: 99%
“…Large-scale genomic rearrangements between wheat allopolyploids [25][26][27][28][29] and between wheat allopolyploids and their progenitor species [30,31] were previously identified. The mechanism(s) of DNA sequence elimination, including deletion of TE-containing sequences following allopolyploidization events, has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%